Stabilization of polypropylene-based materials via molecular retention with hyperbranched polymer. (August 2017) - Matta, Akanksha; Katada, Ikki; Kawazoe, Junji; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract: A novel approach for the stabilization of polypropylene (PP) has been proposed, which is based on the addition of a hyperbranched polymer (HBP) to reversibly trap stabilizer molecules in the dendritic interior and to prevent their volatilization. The lifetime of PP was at maximum 493% elongated by the addition of a small amount of HBP, which itself never suppressed the oxidative degradation, but effectively delayed the volatilization of stabilizers. The stabilization effect of HBP was further signified in the case of PP/SiO2 nanocomposites: HBP was grafted to SiO2 surfaces during melt mixing and was better dispersed through the nanoparticles in the matrix, providing 776% improvement in the lifetime. The versatility of the strategy was also confirmed for a variety of hindered phenols.